The regulatory ecosystem of data driven campaigning in the UK - Barclay, Andrew; Gibson, Rachel; Dommett, Katherine (Frontiers in Political Science, 2023)
Political campaigns are increasingly described as data-driven, as parties collect and analyse large quantities of voter data to target their campaign messages in ever more granular ways, particularly online. These practices have increasingly been facing calls for greater regulation due to the range of harms they are seen to pose for citizens and democracy more generally. Such harms include the intrusions on voter privacy, reduced transparency in how messages are constructed and targeted at voters and exposure to increasingly divisive and polarising political content. Given that data-driven campaigning (DDC) encompasses a range of different practices that are likely to fall under the remit of multiple agencies, it is not evident how suitable current regulatory frameworks are for addressing the harms associated with the growth of DDC. This paper takes a first step toward addressing that question by mapping an emergent regulatory ‘ecosystem’ for DDC in the particular case of the UK. Specifically, we collect and analyse interview data from a range of regulators working directly or indirectly in the election campaigns and communication arena. Our analysis shows that while privacy violations associated with DDC are seen by regulators to be largely well covered by current legislation, other potential harms are given lesser to no priority. These gaps appear to be due to regulators lacking either the powers or the incentives to intervene.